Alternative diagnoses and demographics associated with a raised quantitative faecal immunochemical test in symptomatic patients. (July 2022) - Johnstone, Mark S; Miller, Gillian; Pang, Grace; Burton, Paul; Kourounis, Georgios; Winter, Jack; Crighton, Emilia; Mansouri, David; Witherspoon, Paul; Smith, Karen; McSorley, Stephen T
Background: The faecal immunochemical test (FIT) has proven utility for colorectal cancer detection in symptomatic patients. However, most patients with a raised faecal haemoglobin (f-Hb) do not have colorectal cancer. We investigated alternative diagnoses and demographics associated with a raised f-Hb in symptomatic patients. Methods: A retrospective, observational study was performed of patients with FIT submitted between August 2018 to January 2019 in NHS Greater Glasgow and Clyde followed by colonoscopy. Colonoscopy/pathology reports were searched for alternative diagnoses. Covariables were compared using the χ 2 test. Multivariate binary logistic regression identified independent predictors of a raised f-Hb. Results: 1272 patients were included. In addition to colorectal cancer (odds ratio (OR), 9.27 (95% confidence interval (CI): 3.61–23.83; p < 0.001)), older age (OR, 1.52 (95% CI: 1.00–2.32; p = 0.05)), deprivation (OR, 1.54 (95% CI: 1.21–1.94; p < 0.001)), oral anticoagulants (OR, 1.78 (95% CI: 1.01–3.15; p = 0.046)), rectal bleeding (OR, 1.47 (95% CI: 1.15–1.88; p = 0.002)), advanced adenoma (OR, 7.52 (95% CI: 3.90–14.49; p < 0.001)), non-advanced polyps (OR, 1.78 (95% CI: 1.33–2.38; p < 0.001)) and inflammatory bowel disease (IBD) (OR, 4.19 (95% CI: 2.17–8.07; p < 0.001)) independently predicted raised f-Hb. Deprivation (Scottish Index of Multiple Deprivation (SIMD) 1-2: OR, 2.13 (95% CI: 1.38–3.29; p = 0.001)) independently predicted a raised f-Hb in patients with no pathology found at colonoscopy. Conclusions: An elevated f-Hb is independently associated with older age, deprivation, anticoagulants, rectal bleeding, advanced adenoma, non-advanced polyps and IBD in symptomatic patients. Deprivation is associated with a raised f-Hb in the absence of pathology. This must be considered when utilising FIT in symptomatic patients.